2020
DOI: 10.1049/iet-nbt.2019.0156
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro and in‐vivo evaluation of chitosan‐based thermosensitive gel containing lorazepam NLCs for the treatment of status epilepticus

Abstract: The objective of this study was to develop an in-situ gel containing lorazepam (LZM) loaded nanostructured lipid carriers (NLCs) for direct nose-to-brain delivery in order to increase drug therapeutic efficacy in the treatment of epilepsy. Accordingly, LZM loaded NLCs were formulated using emulsification solvent diffusion and evaporation method; then the effects of the formulation variables on different physicochemical characteristics of NLCs were investigated. Thermosensitive in-situ gels containing LZM-NLCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The IN administration of this formulation achieved a significant reduction of pentylenetetrazole-induced seizures in rats or diminished the seizure intensity compared with a control group and those treated with an in-situ gel containing the free drug, both by IN route; suggesting that the incorporation of NLC into in situ gels could improve the therapeutic drug effect. Moreover, the authors related these outcomes with the small size of NLC, which might allow their transcellular passage by olfactory neurons towards the brain via endocytic pathways of neuronal cells [85].…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
“…The IN administration of this formulation achieved a significant reduction of pentylenetetrazole-induced seizures in rats or diminished the seizure intensity compared with a control group and those treated with an in-situ gel containing the free drug, both by IN route; suggesting that the incorporation of NLC into in situ gels could improve the therapeutic drug effect. Moreover, the authors related these outcomes with the small size of NLC, which might allow their transcellular passage by olfactory neurons towards the brain via endocytic pathways of neuronal cells [85].…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
“…For example, Plasmodium berghei ANKA-injected mice are used to evaluate the anti-cerebral malarial effects of artesunate [ 57 ], artemether, and lumefantrine [ 64 ]. In epilepsy, the maximal electroshock seizure model [ 79 , 80 , 81 ] or pentylenetetrazole-induced epilepsy rat model [ 82 , 83 , 84 ] are used. Treatment effects on Alzheimer’s disease and dementia are assessed using animals with scopolamine-induced amnesia [ 85 , 86 , 87 , 88 , 89 ] or streptozocin-induced Alzheimer’s disease [ 90 ].…”
Section: In Vivo Evaluation Of Intranasal Formulations For Nose-to-br...mentioning
confidence: 99%
“…In mice infected with fungal cells, NLCs (IN) reduced the fungal burden in the brain more than free ketononazole (IN). Taymouri et al developed NLCs containing lorazepam, a drug used to treat epilepsy [ 84 ]. The optimized NLC formulation was loaded into an in situ gel of CS and β-glycerol phosphate for nose-to-brain delivery.…”
Section: In Vivo Evaluations Of Sln and Nlc-based Formulations For No...mentioning
confidence: 99%
See 1 more Smart Citation
“…The combined use of the in situ gel and suitable nanocarriers can allow the further improvement of the formulation effectiveness. For example, an in situ gel based on a mixture of CS and β-glycerol phosphate, containing nanostructured lipid carriers (NLCs) loaded with lorazepam was developed for direct nose-to-brain delivery of the drug; in vivo studies showed that the new “drug-in NLC-in gel formulation” was more effective than the corresponding “drug-in gel formulation” in reducing the pentylenetetrazol-induced seizures, proving its potential usefulness for brain targeting through the nasal route [ 160 ].…”
Section: Chitosan-based Mucosal Drug Delivery Systemsmentioning
confidence: 99%